(untitled) (Journal of Mathematical Study, 2024)
Let M be an n-manifold of positive sectional curvature ≥ 1. In this paper, we show that if the Riemannian universal covering has volume at least v > 0, then the fundamental group π_1(M) has a cyclic subgroup of index bounded above by a constant depending only on n and v.